Cream Skimming, Dregs Skimming, and Pooling: On the Dynamics of Competitive Screening - Diderik Lund; Tore Nilssen (Copenhagen Business School (CBS), Department of Economics, 2003)
We discuss the existence of a pooling equilibrium in a two-period model of an insurance market with asymmetric information. We solve the model numerically. We pay particular attention to the reasons for non-existence in cases where no pooling equilibrium exists. In addition to the phenom- enon of cream skimming emphasized in earlier literature, we here point to the the importance of the opposite: dregs skimming, whereby high-risk consumers are proÞtably detracted from the candidate pooling contract.
hdl:10398/7596
Keywords: D82; G22; L14; 330; Insurance; Insurance Companies; Transactional relationships; Reputation